Análisis Financiero a la Cooperativa de Ahorro y Crédito Las Lagunas, del cantón Saraguro, periodos 2021 – 2022 - Guamán Macau, Mayra Lucia (2024)
This Curricular Integration Work entitled Financial Analysis of the Cooperative of Savings and Credit Las Lagunas, Saraguro canton, periods 2021 - 2022, was prepared in order to analyze the real economic and financial situation of the cooperative and meet the general and specific objectives. Therefore, in order to fulfill the objectives, the vertical analysis was applied to determine the level of percentage participation of each of the accounts that are part of the financial statements and the horizontal analysis to determine the variations (increases and decreases) incurred by the cooperative from one period to another; then the financial performance was analyzed through the application of financial indicators established by the Superintendence of Popular and Solidarity Economy; which leads to the preparation of a financial report containing the results obtained in summary form with conclusions and recommendations. Therefore, through the vertical and horizontal analysis, it was determined that within the financial structure, the account that has the highest participation among the Assets is the Loan Portfolio with an increase of 20.12% in the year 2022, which records the loans granted; for the Liabilities, the Obligations with the Public represented an increase of 20.30%, an account that records the money collected by members and clients; and the Equity reflected 20.50% in the year 2022, corresponding to the contributions of the members and the profit obtained. Regarding the economic structure, income is greater than expenses in both periods, and there was a decrease in profit in 2022 due to higher operating expenses and the income obtained is not as significant compared to the previous year. Similarly, with the application of the financial indicators established by the Superintendency of Popular and Solidarity Economy, it was determined that the indicator of non-performing assets meets the established range, unlike the delinquency rate that exceeds the standard, given that the cooperative has problems in the recovery of loans, and liquidity is 28.40% and 29.24%, therefore, it can respond to its short-term obligations. Finally, a financial report is prepared, which contains a summary of the main results obtained with conclusions and recommendations to help make the right decisions for the cooperative.